BREAK THE MYTH, GROW THE MATH MINDSET: A SYSTEMATIC LITERATURE REVIEW - Megawanti, Priarti; Retnawati, Heri; Basrowi, Ray Wagiu; Rahmadani, Putri (Universitas Labuhanbatu, 2025)
Purpose – This article aims to examine the factors that influence and inhibit a math mindset and how to develop it. Some people still believe in several myths that mathematical intelligence is innate and only suitable for men. This myth not only fosters math anxiety but also hinders the growth of students' mindsets and the achievement of students’ academic goals.Methodology – The method employed is a Systematic Literature Review (SLR) adhering to the PRISMA 2020 guidelines. After carrying out a search process using Publish or Perish for articles indexed by Scopus, 72 articles were obtained as the final result of several selection stages. These articles were reviewed one by one, allowing us to answer the Research Question (RQ) of this study.Findings – The results indicate that two factors contribute to a math mindset, namely internal and external. Meanwhile, factors inhibiting a math mindset include math anxiety, family, and educators, as well as several other factors. Family and educators play important roles in debunking myths and fostering a growth mindset in math.Contribution – The results of this study contribute to the efforts of the government, teachers, and parents in promoting the development of the mathematical mindset in children and students. By understanding that mathematical intelligence can be mastered by everyone without exception, the government, teachers, and parents can jointly implement a curriculum that emphasizes the importance of the learning process rather than the results.